Determination of the properties of Bambusa blumeana using full-culm compression tests and layered tensile tests for finite element model simulation using orthotropic material modeling - Candelaria, Ma. Doreen E.
Construction or building materials are generally selected based on two factors: structural integrity and economical feasibility. However, there is an emerging issue with regards to building materials, and that is sustainability. It already became important to consider the environmental load of a certain construction material. Bamboo's lightweight and flexibility make it a good appealing alternative for residential construction in seismic regions like the Philippines. In this study, bamboo was tested for its material properties using a universal testing machine. Layered tensile tests and full-culm compressive tests were done to get the material properties of the bamboo. These properties were then used to construct an orthotropic material model and simulate the stresses using finite element modeling. The FEM model of a simply-supported beam with a concentrated load at midspan was made. Its cross-section has four orthotropic layers and each layer was modelled with material properties obtained from the experiments. Deflection and normal stresses were obtained from the FEM simulation results. To validate the orthotropic material model for bamboo, three-point bending tests of bamboo beams were conducted and compared with the simulation results. Overall, the top part of the bamboo culm recorded the highest tensile strength per layer, with its outer layers having tensile strength as high as 600 MPa. The recorded tensile strength of its middle and inner layers, on the other hand, were approximately 450 MPa and 180 MPa, respectively. The results from the compressive strength do not exhibit a specific pattern. The top part of the bamboo culm recorded the highest compressive strength with an average of76.84 Mpa. The middle part of the bamboo culm recorded the lowest compressive strength with an average of 62.55 Mpa. The bottom part of the bamboo culm recorded an average compressive strength of 69.49 Mpa. The deflection results from the FEM beam model with orthotropic material is in better agreement with the results from the experiment than the results obtained from the model with isotropic material. On the other hand, the normal stress results fi·om the FEM beam model with isotropic material are closer to the results from the calculations obtained using the transfornled section method of mechanics. This is to be expected because the transformed section method of mechanics assumes isotropic material behaviour. The results show that in modeling the material properties of the bamboo to check for deflections, the orthotropic model gives more accurate results.